2019
DOI: 10.1111/ppa.13065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biological properties of two putative new cytorhabdoviruses infecting Trifolium pratense

Abstract: Three pairs of generic primers designed for specific reverse transcription polymerase chain reaction amplification of part of the cytorhabdoviruses genomes were successfully tested with a number of red clover samples. Two infected plants showing irregular vein clearing, tissue necrosis and stunted growth symptoms were selected for further studies. Subsequently, two novel plant rhabdoviruses, tentatively named Trifolium pratense virus A (TpVA) and Trifolium pratense virus B (TpVB), were detected in red clover p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…At least one transmembrane domain was identified in each P’ protein predicted in the genomes of a group of cytorhabdoviruses discovered in this study, consistent with a previous analysis of other cytorhabdoviruses which also identified at least one transmembrane domain in every P’ protein (Franova et al, 2019). Interestingly, this overprinted accessory protein is encoded by every cytorhabdovirus that appears to be aphid-transmitted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At least one transmembrane domain was identified in each P’ protein predicted in the genomes of a group of cytorhabdoviruses discovered in this study, consistent with a previous analysis of other cytorhabdoviruses which also identified at least one transmembrane domain in every P’ protein (Franova et al, 2019). Interestingly, this overprinted accessory protein is encoded by every cytorhabdovirus that appears to be aphid-transmitted.…”
Section: Discussionsupporting
confidence: 91%
“…At least one transmembrane domain has been predicted in every cytorhabdovirus with an accessory P6 ORF. Transmembrane domains were also predicted in the accessory ORF between G and L genes of other cytorhabdoviruses (Ding et al, 2019; Franova et al, 2019; Yang et al, 2017). Thus, the protein encoded by this small ORF may have membrane-associated functions similar to viroporins in vertebrate rhabdoviruses (Joubert et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At least one transmembrane domain was identified in each P′ protein predicted in the genomes of a group of cytorhabdoviruses discovered in this study, consistent with a previous analysis of other cytorhabdoviruses, which also identified at least one transmembrane domain in every P′ protein [ 65 ]. Interestingly, this overprinted accessory protein is encoded by every cytorhabdovirus that appears to be aphid-transmitted.…”
Section: Discussionsupporting
confidence: 91%
“…The StrV-1-1/2017(B) isolate is maintained to date on cuttings of P. floridana in a greenhouse as recently described [41]. The freeze-dried leaves were deposited in UPOC collection funded by the Ministry of Agriculture of the Czech Republic as a part of the National Program of Genepool Conservation of Microorganisms and Small Animals of Economic Importance () under accession number UPOC-VIR-044.…”
Section: Resultsmentioning
confidence: 99%